Applying the SES Framework to coral reef restoration projects on the Pacific coast of Costa Rica - Palou Zúniga, Nohelia; Madrigal Ballestero, Róger; Schlüter, Achim; Alvarado, Juan José (Revista de Biología Tropical, 2023)
Introduction: Global and local stressors have led to rapid declines in coral reef health. The high rates of coral degradation have motivated restoration initiatives worldwide. Evaluation of these initiatives has provided valuable information regarding coral restoration techniques and limitations faced by projects. However, most of the literature is focused on evaluating metrics related to fragment survival rate and growth, leaving a gap in understanding how social aspects such as governance structure affect project outcomes Objective: The present research applies the Social-Ecological Systems Framework to identify social and ecological factors contributing to the success of three coral reef restoration projects in Costa Rica. Methods: Data was gathered from 50 semi-structured interviews with project members, volunteers, tour operators, fishers, and related community and government organizations that were analyzed using the categories determined by the Social-Ecological Systems Framework. Results: Despite each case’s specific ecological and governance characteristics, research results show that three main steps have contributed to project success. First, the importance of locals having a positive perception of coral reef and project benefits; second, the use of network structure to obtain adequate financial and human resources and third, the importance of compliance with a regulatory framework to create enabling environments for reef restoration. Conclusions: Results show no universal solutions for coral reef restoration projects. Project managers must understand the ecological and social context of the restoration site to boost the benefits that reef restoration projects can provide, such as an increase in local stewardship, income generation, and the creation of more resilient communities.